INTEGRATING PHYSIOLOGICAL AND PSYCHOLOGICAL TECHNIQUES TO MEASURE AND IMPROVE USABILITY: AN EMPIRICAL STUDY ON KINECT APPLYING OF HEALTH MANAGEMENT SPORT - Cheng, Wei-Ying; Huang, Po-Hsin; Chiu, Ming-Chuan (International Journal of Industrial Engineering: Theory, Applications and Practice, 2014)
This research aimed to develop an approach for measuring, monitoring and auditing the usability of a motion-related health management product. Based on an ergonomic perspective and principles, the interactions between test participants and a motion sports device were studied using physiological data gathered from a heart rate sensor. Based on our literature review, we customized a psychological usability questionnaire which considered effectiveness, efficiency, satisfaction, error, learnability, sociability, and mental workload, generating a tool meant to reveal the subjective cognition of product usability. This research analyzed the objective (physiological) and subjective (psychological) data simultaneously to gain greater insight about the product users. In addition, heart rate data, mental workload data and the questionnaire data were synthesized to generate a comprehensive, detailed approach for evaluating usability in order to provide suggestions for improving the usability of an actual health care product.